Treatment of wastewater originating from aquaculture and biomass production in laboratory algae bioreactor using different carbon sources - Velichkova, Katya N.; Sirakov, Ivaylo N.; Beev, Georgi G.; Denev, Stefan A.; Pavlov, Dimitar H. (Penerbit Universiti Kebangsaan Malaysia, 2016)
The aim of present study was to explore the effect of different carbon sources on biomass accumulation in microalgae Nannochloropsis oculata and Tetraselmis chuii and their ability to remove N and P compounds during their cultivation in aquaculture wastewater. Microalgae cultivation was performed in laboratory bioreactor consisted from 500 mL Erlenmeyer flasks, containing 250 mL wastewater from semi closed recirculation aquaculture system. The cultures were maintained at room temperature (25-27ºC) on a fluorescent light with a light: dark photoperiod of 15 h: 9 h. The microalgae species were cultivated in wastewater with different carbon sources: glucose, lactose and saccharose. The growth of strains was checked for 96 h period. In the present study, N. oculata and T. chuii showed better growth in wastewater from aquaculture with saccharose carbon source during the experiment. The most effective reduce of nitrate and total nitrogen was proved in N. oculata cultivated in wastewater with glucose as carbon source. T. chuii cultivated in wastewater containing glucose showed 8.27% better cleaning effect in ammonium compared with N. oculata. T. chuii grew in wastewater with glucose as carbon source showed 19.5% better removal effect in phosphate compared with N. oculata strain.